Oral History Program Interview: Goldie Mae Jarrell Farris - Farris, Goldie Mae Jarrell
Born in Gainesville, Cooke County, Texas about 1928, Farris later traveled to Tulare, California in 1939 with her family. She recounts the border searches; discrimination religiously, as a migrant, and educationally; the appalling lack of medical care in ditch camps; her life in a government camp; how "Okie" was worse than Texan; the essential nature of food stamps for survival; and The Grapes of Wrath as very accurate.